Traceability of Prêt à Porter Clothing through Cryptographic Protocols - Araceli Queiruga-Dios; Juan José Bullón Pérez; Ángel Martín del Rey (Proceedings, 2017)
In recent years, several methods for monitoring processes and different types of activities have been developed as characteristic of the connected industry and Internet of Things (IoT). [...]